Ultra-high performance concrete and composite material combined foot plank
By combining ultra-high performance concrete with composite ribs, the problems of insufficient durability and high cost of walking plates are solved, and the pedestrian plate with high mechanical properties and long life are achieved, reducing the plate weight and production costs.
Patent Information
- Application Number
- CN202411207062.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-27
AI Technical Summary
Existing pedestrian boards either use ordinary concrete or rubber materials to cause insufficient durability, or use composite pedestrian boards with higher cost.
Walking boards using ultra-high performance concrete and composite materials, high performance concrete slab surface and weaving composite material ribs. The composite material ribs are made of glass fiber roving, glass fiber felt and polyurethane resin, and obtained through pultruding process system. , used in combination to improve the mechanical properties of the walking board and reduce costs.
It realizes the high mechanical properties, impact resistance and fatigue resistance of pedestrian boards, extends service life, and reduces the board weight and production costs. Compared with pure composite pedestrian boards, it can reduce the use of composite materials by 75% and reduces the cost by 60%. %.
Smart Images

Figure CN119191781A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a walking board composed of ultra-high performance concrete and a composite material, belonging to the technical field of walking boards. Background Art
[0002] As an important part of the auxiliary facilities of railway bridge decks, walking boards are mainly used as covers for cable troughs in railway bridges, stations, roadbeds, tunnels and other projects, as well as walking boards for personnel and small machines to pass through. At present, the walking boards used on railway bridge decks are mainly reinforced concrete walking boards. However, reinforced concrete walking boards are heavy, which increases the design strength of the bridge structure and the time and difficulty of installation, construction, maintenance and replacement. In addition, they deteriorate severely in severe cold and strong ultraviolet radiation environments, and replacement is time-consuming and labor-intensive. These problems not only affect the installation efficiency of walking boards, but also cause certain safety hazards.
[0003] In recent years, in order to reduce the deadweight of the bridge and reduce the maintenance workload of the bridge maintenance department. Existing sidewalk boards are usually made of rubber as the main material, and rubber walking boards, as well as various composite walking boards, have also begun to be tried. For example, patent application number CN202320495264.3 introduces a rubber walking board, and patent application numbers CN202410127989.6. and CN202322164354.7 each introduce a fiber-reinforced composite walking board. During the use of rubber walking boards, it is easy to be affected by the combined effects of various internal and external factors, causing the physical, chemical and mechanical properties of rubber to gradually deteriorate, and finally lose its use value, that is, aging. Moreover, when the ambient temperature is high, the elastic modulus of the rubber walking board is significantly reduced, and the deformation under the action of pedestrian load increases, which makes people feel insecure. The production process of compression molded composite walking boards is affected by factors such as temperature, molding pressure, and molding time. Even if the raw materials, structural forms, and sizes of the walking boards are exactly the same, it is difficult to maintain uniform quality for different walking boards. Different parts of the same walking board have different physical and mechanical properties due to different fiber contents. Pultrusion molded composite walking boards use glass fiber or basalt fiber as reinforcement materials. Fiber mats can be added to increase lateral strength. It is an excellent and economical profile production method, which is very suitable for mass production of high-quality fiber-reinforced composite profiles. However, the overall cost of fiber-reinforced composite materials is high, making it difficult to open up the market on a large scale. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In order to solve the problem that the walking boards in the prior art either use ordinary concrete or rubber materials resulting in insufficient durability, or use composite walking boards with high costs, the present invention provides a walking board combining ultra-high performance concrete and composite materials.
[0006] (II) Technical solution
[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0008] A walking board composed of ultra-high performance concrete and composite materials, comprising a high-performance concrete board surface and composite material ribs embedded therewith, wherein the high-performance concrete board surface is prepared by 800-1000 parts by mass of P·O52.5 cement, 0-150 parts by mass of fly ash, 0-150 parts by mass of silica fume, 1000-1200 parts by mass of river sand, 20-30 parts by mass of polycarboxylic acid water reducing agent, 0-5 parts by mass of defoaming agent, 0-200 parts by mass of steel fiber, and 150-180 parts by mass of mixing water;
[0009] The composite material rib is made of glass fiber roving, glass fiber mat and polyurethane resin, and is obtained by a pultrusion process system, wherein the pultrusion process system includes the glass fiber roving and glass fiber mat being dipped in liquid polyurethane resin, heated and cured, extruded and cut to length under external traction.
[0010] The walking board as described above, preferably, the P·O52.5 cement is 800-900 parts, fly ash is 70-100 parts, silica fume is 70-100 parts, river sand is 1050-1150 parts, polycarboxylic acid water reducer is 25-28 parts, defoamer is 0.5-2 parts, steel fiber is 100-200 parts, water is 160-170 parts;
[0011] The composite material rib comprises 50 to 70 parts by weight of glass fiber roving, 10 to 30 parts by weight of glass fiber mat and 18 to 25 parts by weight of polyurethane resin.
[0012] Further preferably, the P·O52.5 cement is 850 parts, fly ash is 75 parts, silica fume is 75 parts, river sand is 1100 parts, polycarboxylic acid water reducer is 26 parts, defoamer is 1 part, steel fiber is 117 parts, water is 161 parts; the glass fiber roving is 50 parts, glass fiber mat is 20 parts and polyurethane resin is 25 parts. Further, the polyurethane resin is composed of isocyanate and polyether polyol in a mass ratio of 1.2:1.
[0013] For the walking board as described above, preferably, the silica fume is a densified silica fume with a silica content of 92%, the polycarboxylic acid-based water reducer is a standard polycarboxylic acid water reducer, the defoamer is an organosilicon defoamer, and the steel fiber is a 13 mm double-ended copper-plated steel fiber with a hook.
[0014] As for the walking board as described above, preferably, the composite material rib is in the shape of an I-shaped rib, one end of which is embedded in the ultra-high performance concrete board surface, and the other end extends out of the ultra-high performance concrete board surface.
[0015] For the walking board as described above, preferably, the length of one end of the upper and lower ends of the composite material rib is greater than the length of the other end; the longer end is buried in the ultra-high performance concrete board surface.
[0016] For the walking board as described above, preferably, the thickness of the high-performance concrete board surface is 10-50 mm, the length of one end of the composite material rib is 20-35 mm, the length of the other end is 15.5-30 mm, the width of the middle connecting part is 5-10 mm, and the height is 40 mm-60 mm.
[0017] In the walking board as described above, preferably, the composite material ribs are provided in 2 to 6 numbers, and the length of the composite material ribs embedded in the ultra-high performance concrete is 1 / 3 to 1 / 2 of the composite material ribs.
[0018] The preparation method of the walking board as described above comprises mixing high-performance concrete according to various components to form an ultra-high-performance concrete slurry, pouring it into a mold, pressing the composite material rib into the ultra-high-performance concrete slurry, and keeping the shape fixed.
[0019] When in use, the walking board prepared by the present invention can be directly set up on the installed sidewalk bridge frame to form a railway bridge sidewalk.
[0020] (III) Beneficial effects
[0021] The beneficial effects of the present invention are:
[0022] The present invention provides a walking board made of ultra-high performance concrete and composite materials. By using ultra-high performance concrete as the board surface of the walking board, the ultra-high performance concrete has higher mechanical properties (flexural strength, compressive strength), better impact resistance, fatigue resistance, and is not easy to fail under the action of cyclic loads. It has a longer service life and can solve the problem of insufficient durability of ordinary concrete. The ribs made of composite materials are used as the lower structure to withstand tensile stress. This combination can use about 75% less composite materials than pure composite material walking boards.
[0023] The present invention provides a combined structure railway bridge walking board formed by combining ultra-high performance concrete and composite materials. The walking board uses ultra-high performance concrete as the board surface and glass fiber reinforced polyurethane composite materials as the ribs, both of which have the advantages of high strength and high corrosion resistance, longer service life, and are lighter than ordinary concrete walking boards. The board's deadweight can be reduced by about 65%, making it more convenient to install and transport. Compared with pure composite walking boards, the cost is reduced by about 60%. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the walking board in Example 1;
[0025] Figure 2 This is the cross section of the walking board in Example 1;
[0026] Figure 3 Detailed dimensions of Example 1;
[0027] Figure 4 This is a schematic diagram of a walking board in Example 2;
[0028] Figure 5 This is the cross section of the walking board in Example 2;
[0029] Figure 6 The detailed dimensions of the walking board in Example 2;
[0030] Figure 7 It is a reinforcement diagram;
[0031] Figure 8 It is a loading diagram;
[0032] Fig. 9 Loading diagram for normal concrete slab;
[0033] Fig.10 The crack condition of ordinary concrete slab when the load is 2.0 times;
[0034] Fig.11 This is the crack condition of ordinary concrete slab after unloading;
[0035] Fig.12 The cracks of the reinforced 30 mm thick UHPC walking slab after unloading;
[0036] Fig.13 Loading diagram for composite ribbed ultra-high performance concrete slab;
[0037] Fig.14 Crack condition of ultra-high performance concrete slab with composite ribs after unloading. DETAILED DESCRIPTION
[0038] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0039] Example 1
[0040] The walking board includes a board surface made of ultra-high performance concrete and an I-shaped rib made of a composite material, wherein the ultra-high performance concrete is prepared by weight, 800-1000 parts of P·O52.5 cement, 0-150 parts of fly ash, 0-150 parts of silica fume, 1000-1200 parts of river sand, 20-30 parts of polycarboxylic acid water reducer, 0-5 parts of organic silicon defoamer, 0-200 parts of hook-shaped steel fiber, and 150-180 parts of mixing water. After the mixing is completed, it is poured into the mold and vibrated for about 30 seconds, and then the I-shaped rib of the composite material is pressed into the ultra-high performance concrete slurry and the shape is kept fixed. Among them, the composite material composition of the I-shaped rib is obtained by a conventional pultrusion molding process using 50 to 70 parts by mass of glass fiber roving, 10 to 30 parts by mass of glass fiber mat and 18 to 25 parts by mass of polyurethane resin. Specifically, the glass fiber roving and glass fiber mat are pulled by external force, impregnated with liquid polyurethane resin, heated and cured, extruded and cut to a fixed length.
[0041] like Figure 1 As shown, the surface of the walking board is made of 20mm thick ultra-high performance concrete. Different sizes of walking boards can be produced according to different molds. The lower part uses bench-like composite material I-shaped ribs as support, and the two are combined together through prefabrication. The I-shaped ribs on both sides have one end larger than the other end, such as Figure 2 The larger end is buried in the ultra-high performance concrete as a force transmission structure, and the other end extends out of the concrete floor surface, which can increase the overall thickness of the floor and improve the lateral stiffness of the floor. At the same time, the ultra-high performance concrete can be completely in the compression zone to avoid cracking of the concrete when bearing load; the web is in contact with the concrete, which is not only convenient for operation during prefabrication, but also provides a layer of constraint to the upper concrete floor when the floor is under stress to enhance the bearing capacity. For the detailed dimensions of the I-shaped rib, please refer to Figure 3 The I-shaped rib has a cross-sectional area of 20 mm long at one end and a thickness of 4 mm, and a cross-sectional area of 15.5 mm long at the other end. The middle connecting part has a width of 5 mm and a length of 28 mm. The overall height of the I-shaped rib is 40 mm, and the height immersed in concrete is half of the entire I-shaped rib.
[0042] Example 2
[0043] The panel surface of this embodiment also adopts the ultra-high performance concrete of the embodiment 1, except that Figure 4 As shown in the figure, the thickness of the board is 30mm, and four I-shaped ribs are used as support parts to bear the tensile stress at the bottom. Figure 5 As shown in the figure, the larger end of the I-shaped rib is buried in the ultra-high performance concrete as a force transmission structure, and the other end extends out of the concrete, which can increase the overall thickness of the slab and improve the lateral stiffness of the slab. The specific dimensions of the I-shaped rib in the concrete are shown in Figure 6 As shown, the height immersed in concrete is 13 mm.
[0044] Example 3
[0045] The walking board was prepared according to the preparation method in Example 1 and the load-bearing capacity was compared with that of ordinary concrete walking boards.
[0046] 1. Test plate forming
[0047] (1) The test used a mold with a specification of 1580*405*80mm to form two parallel samples of the step plates listed in Table 1, and compared the bearing capacity and crack resistance.
[0048] Table 1 Reinforcement design of different plates
[0049]
[0050] The remark number format is concrete-slab thickness-description, PC stands for ordinary concrete, UHPC stands for ultra-high performance concrete, W stands for no reinforcement, G stands for reinforced concrete, and F stands for composite ribs.
[0051] (2) The mix ratio information used in the test is shown in Table 2.
[0052] Table 2 Concrete mix ratio (unit: kg / m 3 )
[0053]
[0054] The cement used in both PC and UHPC is P·O52.5 cement, the water reducer is a standard polycarboxylic acid water reducer, the defoamer in UHPC is silicone defoaming powder, and the steel fiber is a 13mm double-ended copper-plated steel fiber with hooks.
[0055] The composite material rib is prepared by conventional pultrusion molding process with 50 parts of glass fiber roving, 20 parts of glass fiber mat and 25 parts of polyurethane resin by weight, wherein the polyurethane resin is composed of isocyanate and polyether polyol with a mass ratio of 1.2:1. Specifically, the glass fiber roving and glass fiber mat are dipped in liquid polyurethane resin under external traction, wherein the injection pressure is 1.5MPa-2.0MPa, the pultrusion speed is 0.3m / min, and the heated and cured mold is divided into three heating zones, with the front zone temperature of 120℃, the middle zone temperature of 150℃, and the rear zone temperature of 180℃ for continuous extrusion.
[0056] (3) Reinforcement description
[0057] ① For steel bars, the reinforcement is in the form of single-layer reinforcement, such as Figure 7The upper layer consists of 7 structural bars of φ8@190mm, and the lower layer consists of 4 tensile bars of φ8@80mm, which are tied with oak wire.
[0058] For 30mm slabs, the protective layer thickness is 8mm; for 70mm slabs, the protective layer thickness is 20mm, where the protective layer thickness refers to the minimum distance from the concrete surface to the outer edge of the nominal diameter of the outermost steel bar.
[0059] 2. Test loading
[0060] The loading test is carried out in accordance with Appendix E of Railway Cable Tray Covers and Sidewalk Steps: Part 1 (Q / CR2.1-2014), as follows:
[0061] (1) Loading method
[0062] The simulation test is carried out by using single-point concentrated loading, the loading equipment uses a hydraulic jack, and a pressure sensor is used to accurately measure the load value. Figure 8 The reverse loading method shown, with the bottom of the plate facing upward, is conducive to observing the cracking phenomenon of the tensile surface. The pad is made of 60mm×60mm×20mm steel plate.
[0063] (2) Design load calculation
[0064] A concentrated equivalent load is applied at the midpoint of the plate. The distribution area of the concentrated load (with a steel pad underneath) is 60mm×60mm. The effect of the concentrated equivalent load is similar to the design vertical static and live load, that is, the equivalent concentrated load is determined based on the principle of equal maximum tensile stress generated at the bottom of the plate.
[0065] According to the standard requirements, the bearing capacity of the sidewalk tread should meet 1.5kN concentrated load and 5kN / m 2 The uniformly distributed load force requirement is calculated based on the plate area to obtain an equivalent concentrated load of 1.5+5×1.58×0.4=4.66kN
[0066] (3) Loading steps
[0067] After the test piece is installed in place, the test equipment, support distance and pad are carefully checked. After confirmation, loading begins. The loading speed is required to be slow and uniform. A 50t hydraulic jack is used for manual loading, and a pressure sensor with an accuracy of 1N and a range of 20KN is used for precise measurement, so that the loading rate is not greater than 100N / s. The load levels are divided into: 0, 0.5, 1.0, 1.2, and 2.0 times the equivalent concentrated load. After the cover plate is loaded to each level of load, the load is maintained for 3 minutes, and the bottom of the cover plate is observed with a crack width detector during the entire loading process. The load when cracks appear is the cracking load.
[0068] When testing the anti-cracking performance of the cover plate, you can load it to 1.2 times the equivalent concentrated load. When testing the bearing capacity of the cover plate, you can load it to 2.0 times the equivalent concentrated load. If necessary, continue to load until the cover plate is destroyed.
[0069] 3. Test results and analysis
[0070] The loading test results are shown in Table 3.
[0071] Table 3 Statistics of cracking load, ultimate load and maximum crack width (mm) of each group of plates at each loading level
[0072]
[0073] Note: F in the table 裂 represents the cracking load, F 极 represents the ultimate load, F 等 is the equivalent concentrated load, and represents the situation where no measurement is required.
[0074] No. 1 is a common concrete walking slab PC-70-G. When loaded Fig. 9 It can be seen that the crack resistance and bearing capacity of ordinary concrete slabs meet the requirements. There is no crack under 1.2 times the equivalent concentrated load, and it can still bear the load under 2.0 times the equivalent concentrated load. Fig.10 As shown, the crack width is greater than or equal to 0.5 mm. The crack condition after unloading is as follows Fig.11 In this experiment, the load when the crack width is greater than 0.5 mm is recorded as the ultimate load.
[0075] No. 2 is an unreinforced ultra-high performance concrete walking slab UHPC-30-W. Since there is no steel bar to bear direct force, the displacement deformation develops very quickly when subjected to load, and the number of cracks on the bottom surface of the slab develops rapidly. As the pressure increases, the deformation of the slab continues to increase. When the bending deformation reaches the maximum, the ultimate load of the slab is 4.1-4.2kN. It can be seen that although the unreinforced ultra-high performance concrete slab does not break under the load, the bending deformation is too large, which affects the bearing capacity. The crack situation after unloading is as follows Fig.12 shown.
[0076] No. 3 is an ultra-high performance concrete walking board UHPC-30-G with steel bars. From the results, it can be seen that at 2.33kN, cracks have already occurred at the bottom of the board, but the cracks are small. They cannot be distinguished by the naked eye and can only be seen with the help of a crack width detector. When the load reaches 4.66kN, the cracks further develop and reach about 0.1mm. At this time, the direction and distribution of the cracks can be clearly seen by the naked eye. As the loading continues, the cracks gradually increase and recover after unloading.
[0077] No. 4 is an ultra-high performance concrete walking board UHPC-30-F with embedded composite material ribs of the present invention, and the loading form is as follows: Fig.13 There is no cracking when the load is 0.5 times (2.33kN). When the load is 1.0 times (4.66kN), fine cracks appear on the bottom surface of the board, and the crack width increases with the thickness of the board. Due to the high durability of composite materials, the fine cracks do not affect the durability of the board. As the load gradually increases to 2.0 times, the cracks on the bottom of the board increase to 0.1mm. When the load is continued to be 4.0 times, the bearing capacity is much higher than that of ordinary concrete slabs with a thickness of 70mm and ultra-high performance concrete walking slabs with steel bars. When the load is unloaded, the crack width is reduced to less than 0.05mm. Fig.14 In order to make the picture clearer, a black pen has been used to mark the cracks. The arrow in the figure points to the cracks marked with the black pen. This shows that the composite material ribs that bear the tensile force undergo elastic-plastic deformation under the action of load. At the same time, it was found in the test that due to the presence of the composite material ribs, the cracks at the bottom of the board are separated and no longer connected. Instead of forming a continuous crack, multiple small cracks in multiple sections are formed, which hinder the development of the cracks to a certain extent, thereby extending its service life. Therefore, by comparison, it is shown that the ultra-high performance concrete walking board with embedded composite material ribs provided by the present invention is not easy to fail under the action of load, has a longer service life, and solves the problem of insufficient durability of ordinary concrete.
[0078] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A walking board composed of ultra-high performance concrete and composite materials, characterized in that: The high-performance concrete slab comprises a high-performance concrete slab and a composite material rib embedded therewith, wherein the high-performance concrete slab comprises, by weight, 800 to 1000 parts of P·O52.5 cement, 0 to 150 parts of fly ash, 0 to 150 parts of silica fume, 1000 to 1200 parts of river sand, 20 to 30 parts of a polycarboxylic acid water reducing agent, 0 to 5 parts of a defoaming agent, 0 to 200 parts of steel fiber, and 150 to 180 parts of water; The composite rib is made of glass fiber roving, glass fiber mat and polyurethane resin and is obtained by a pultrusion process system.
2. The walking board according to claim 1, characterized in that: The P·O52.5 cement is 800-900 parts, fly ash is 70-100 parts, silica fume is 70-100 parts, river sand is 1050-1150 parts, polycarboxylic acid water reducer is 25-28 parts, defoamer is 0.5-2 parts, steel fiber is 100-200 parts, and water is 160-170 parts; The glass fiber roving is 50 to 70 parts, the glass fiber mat is 10 to 30 parts, and the polyurethane resin is 18 to 25 parts.
3. The walking board according to claim 1, characterized in that: The P·O52.5 cement is 850 parts, fly ash is 75 parts, silica fume is 75 parts, river sand is 1100 parts, polycarboxylic acid water reducer is 26 parts, defoamer is 1 part, steel fiber is 117 parts, and water is 161 parts.
4. The walking board according to claim 1, characterized in that: The glass fiber roving accounts for 50 parts, the glass fiber mat accounts for 20 parts, and the polyurethane resin accounts for 25 parts.
5. The walking board according to claim 1, characterized in that: The silica fume is a densified silica fume with a silicon dioxide content of 92%, the polycarboxylic acid water reducer is a standard polycarboxylic acid water reducer, the defoamer is an organic silicon defoamer, and the steel fiber is a 13 mm double-ended hook-type copper-plated steel fiber.
6. The walking board according to claim 1, characterized in that: The polyurethane resin is composed of isocyanate and polyether polyol in a mass ratio of 1.2:
1.
7. The walking board according to claim 1, characterized in that: The composite material rib is in the shape of an "I"-shaped rib, one end of which is buried in the ultra-high performance concrete and the other end extends out of the concrete.
8. The walking board according to claim 7, characterized in that: The length of one end of the upper and lower ends of the composite material rib is greater than that of the other end; the longer end is buried in the ultra-high performance concrete.
9. The walking board according to claim 7, characterized in that: The thickness of the high performance concrete slab is 10-50mm, the length of one end of the composite material rib is 20-35mm, the length of the other end is 15.5-30mm, the width of the middle connection part is 5-10mm, and the height is 40mm-60mm.
10. The walking board according to claim 1, characterized in that: There are 2 to 6 composite material ribs, and the length of the composite material ribs buried in the ultra-high performance concrete is 1 / 3 to 1 / 2 of the composite material ribs.
